A survey for variable young stars with small telescopes: II – mapping a protoplanetary disc with stable structures at 0.15 au. Issue 1 (20th January 2020) - Evitts, Jack J; Froebrich, Dirk; Scholz, Aleks; Eislöffel, Jochen; Campbell-White, Justyn; Furnell, Will; Stecklum, Bringfried; Urtly, Thomas; Pickard, Roger; Wiersema, Klaas; Dubovský, Pavol A; Kudzej, Igor; et al.
ABSTRACT: The HOYS citizen science project conducts long-term, multifilter, high-cadence monitoring of large YSO samples with a wide variety of professional and amateur telescopes. We present the analysis of the light curve of V1490 Cyg in the Pelican Nebula. We show that colour terms in the diverse photometric data can be calibrated out to achieve a median photometric accuracy of 0.02 mag in broad-band filters, allowing detailed investigations into a variety of variability amplitudes over time-scales from hours to several years. Using Gaia DR2, we estimate the distance to the Pelican Nebula to be 870 ^+70_-55 pc. V1490 Cyg is a quasi-periodic dipper with a period of 31.447 ± 0.011 d. The obscuring dust has homogeneous properties, and grains larger than those typical in the ISM. Larger variability on short time-scales is observed in U and Rc −H α, with U amplitudes reaching 3 mag on time-scales of hours, indicating that the source is accreting. The H α equivalent width and NIR/MIR colours place V1490 Cyg between CTTS/WTTS and transition disc objects. The material responsible for the dipping is located in a warped inner disc, about 0.15 au from the star. This mass reservoir can be filled and emptied on time-scales shorter than the period at a rate of up to 10 −10 M⊙ yr −1, consistent with low levels of accretion in other T Tauri stars. Most likely, the warp at this separation from the star is induced by a protoplanet in the inner accretion disc. However, we cannot fully rule out the possibility of an AA Tau-like warp, or occultations by the Hill sphere around a forming planet.